Model of developing professional thinking in modern education conditions - Kodekova, Galiya; Mukatayeva, Kundyz; Korvyakov, Valeriy; Auyezova, Zaure; Turganbayeva, Beibitgul (Opción, 2019)
The problem of development of professional thinking at students is considered in the given article. The empirical data on the basis of diagnostic material were obtained by the pilot and experimental way. Results of diagnostics of an initial condition of understanding on the studied phenomenon allowed to determine the main directions of work on the development of professional thinking. The received results of the research will allow to improve the pedagogical process in higher education institution as the modern education system, places more and greater demands on the personality of the future specialist.